2020
DOI: 10.1128/msphere.00939-19
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evolution Experiments Help Identify a Predominant Region of Constitutive Stable DNA Replication Initiation

Abstract: The bacterium Escherichia coli can initiate replication in the absence of the replication initiator protein DnaA and/or the canonical origin of replication oriC in a ΔrnhA background. This phenomenon, which can be primed by R-loops, is called constitutive stable DNA replication (cSDR). Whether DNA replication during cSDR initiates in a stochastic manner through the length of the chromosome or at specific sites and how E. coli can find adaptations to loss of fitness caused by cSDR remain inadequately answered. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…In recent studies, replication profiles revealed in more detail the locations where cSDR is initiated, which are reasonably well-defined, including one particularly strong site roughly 500-600 kb clockwise from oriC at ∼4.5 Mbp, as well as a peak of synthesis in the termination area (Maduike et al, 2014;Dimude et al, 2015;Veetil et al, 2020). Despite a detailed analysis of the locations of initiation sites, the precise molecular mechanism that triggers the initiation of DNA synthesis in these defined locations is not fully understood (Maduike et al, 2014;Dimude et al, 2015;Veetil et al, 2020).…”
Section: Dna Replication In Cells Without Active Replication Originsmentioning
confidence: 99%
“…In recent studies, replication profiles revealed in more detail the locations where cSDR is initiated, which are reasonably well-defined, including one particularly strong site roughly 500-600 kb clockwise from oriC at ∼4.5 Mbp, as well as a peak of synthesis in the termination area (Maduike et al, 2014;Dimude et al, 2015;Veetil et al, 2020). Despite a detailed analysis of the locations of initiation sites, the precise molecular mechanism that triggers the initiation of DNA synthesis in these defined locations is not fully understood (Maduike et al, 2014;Dimude et al, 2015;Veetil et al, 2020).…”
Section: Dna Replication In Cells Without Active Replication Originsmentioning
confidence: 99%
“…On homology-based recombination, long repeats lead to deletion or duplication of the genomic segment or inversion of the region flanked by them. Laboratory evolution studies from various groups in different genomes of Escherichia, Bacillus , and Salmonella have shown that these structural variations affect bacterial fitness in different stresses and can be adaptive in nature under different conditions (Veetil et al 2020; Srinivasan et al 2015; Rocha et al 1999; Sonti & Roth 1989; Maharjan et al 2013; Achaz et al 2003). Different types of structural variations in the genome impact bacteria differently.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the position of a gene can lead to changes in their dosage and thus expression; this might further hamper bacterial growth (Bryant et al 2014). Alternatively, any shift in the position of the oriC or a disruption of oriC functioning, can impact gene expression on a global scale and might be substantially deleterious for the bacteria (Veetil et al 2020; Dimude et al 2018; Bryant et al 2014; Duigou & Boccard 2017). Changes in gene orientation, caused by inversions, might result in head-on collisions of DNA and RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations